Exploring the biotechnological potential of novel soil-derived Klebsiella sp. and Chryseobacterium sp. strains using phytate as sole carbon source - Maldonado-Pava, Julieth; Tapia-Perdomo, Valentina; Estupinan-Cardenas, Liliana; Puentes-Cala, Edinson; Castillo-Villamizar, Genis Andrés (Frontiers in Bioengineering and Biotechnology, 2024)
Phosphorus (P) is essential for biological systems, playing a pivotal role in energy metabolism and forming crucial structural components of DNA and RNA. Yet its bioavailable forms are scarce. Phytate, a major form of stored phosphorus in cereals and soils, is poorly bioavailable due to its complex structure. Phytases, enzymes that hydrolyze phytate to release usable phosphorus, are vital in overcoming this limitation and have significant biotechnological applications. This study employed novel method to isolate and characterize bacterial strains capable of metabolizing phytate as the sole carbon and phosphorus source from the Andes mountains soils. Ten strains from the genera Klebsiella and Chryseobacterium were isolated, with Chryseobacterium sp. CP-77 and Klebsiella pneumoniae CP-84 showing specific activities of 3.5 ± 0.4 nkatal/mg and 40.8 ± 5 nkatal/mg, respectively. Genomic sequencing revealed significant genetic diversity, suggesting CP-77 may represent a novel Chryseobacterium species. A fosmid library screening identified several phytase genes, including a 3-phytase in CP-77 and a glucose 1-phosphatase and 3-phytase in CP-84. Phylogenetic analysis confirmed the novelty of these enzymes. These findings highlight the potential of phytase-producing bacteria in sustainable agriculture by enhancing phosphorus bioavailability, reducing reliance on synthetic fertilizers, and contributing to environmental management. This study expands our biotechnological toolkit for microbial phosphorus management and underscores the importance of exploring poorly characterized environments for novel microbial functions. The integration of direct cultivation with metagenomic screening offers robust approaches for discovering microbial biocatalysts, promoting sustainable agricultural practices, and advancing environmental conservation.